Rhes Is Involved in Striatal Function - Spano, Daniela (American Society for Microbiology, 2004)
The development and the function of central nervous system depend on thyroid hormones. In humans, the lack of thyroid hormones causes cretinism, a syndrome of severe mental deficiency. It is assumed that thyroid hormones affect the normal development and function of the brain by activating or suppressing target gene expression because several genes expressed in the brain have been shown to be under thyroid hormone control. Among these, the Rhes gene, encoding a small GTP-binding protein, is predominantly expressed in the striatal region of the brain. To clarify the role of Rhes in vivo, we disrupted the Rhes gene by homologous recombination in embryonic stem cells and generated mice homozygous for the Rhes null mutation (Rhes(−/−)). Rhes(−/−) mice were viable but weighed less than wild-type mice. Furthermore, they showed behavioral abnormalities, displaying a gender-dependent increase in anxiety levels and a clear motor coordination deficit but no learning or memory impairment. These results suggest that Rhes disruption affects selected behavioral competencies.